A biomimetic compound eye lens for photocurrent enhancement at low temperatures. (1st July 2022) - Han, Sanghu; Sung, Jaebum; Ko, Byeongjo; Kwon, Minjun; Kim, Sewon; So, Hongyun
Abstract: In this study, an artificial compound eye lens (ACEL) was fabricated using a laser cutting machine and polyvinyl alcohol (PVA) solution. A laser cutter was used to punch micro-sized holes (500  μ m diameter—the smallest possible diameter) into an acrylic plate; this punched plate was then placed on the aqueous PVA solution, and the water was evaporated. The plate was used as the mold to obtain a polydimethylsiloxane (PDMS) micro lens array film, which was fixed to a dome-shaped three-dimensional-printed mold for further PDMS curing, and a hemispherical compound eye lens was obtained. Using a gallium nitride (GaN) photodetector, a light detection experiment was performed with the ACEL, bare lens, and no lens by irradiating light at various angles under low temperatures. The photodetector with the ACEL generated a high photocurrent under several conditions. In particular, when the light was irradiated at 0° and below −20 °C, the photocurrent of the GaN sensor with the ACEL increased by 61% and 81% compared with the photocurrent of the GaN sensor with the bare lens and without a lens, respectively. In this study, a sensor for detecting light with ACEL was demonstrated in low-temperature environments, such as indoor refrigerated storages and external conditions in Antarctica and Arctic.